The leisure as a promoter practice in the mental health in the community: experience report - Janaína Paula Calheiros Pereira Sobral; Alana Maiara Brito Bibiano; Nívia Madja dos Santos Silva; Jocelene Gonçalves de Almeida; Mariana Gomes Lima Avelino; Amanda Maria Monteiro Ferreira (Universidad de Alicante, 2019)
Leisure is one of the conditions and health determinants and it participates in the health-disease process, especially in the context of mental health. Thus, the aim of this study was to describe the experience of multidisciplinary residents in family health in the planning and implementation of mental health promotion actions through leisure activities in the community adscript in a Family Health Unit in Maceió, Alagoas. It was observable during the process of territorialisation, the lack of leisure devices and spaces reception to the demands of mental health of the population, and it was carried out various actions, through weekly meetings in order to create recreational spaces, interaction and media, in addition to encouraging sustainability and promote income generation. It was noticed that the leisure activities provided greater community involvement from socializing moments, increased formation of bond between the population and the health team, increasing self-esteem, improving care for the body and mind, and stimulated income generation and care for the environment through recycled material recycling workshops.